Understanding perpetual R&D races - Yves Breitmoser; Jonathan H. W. Tan; Daniel John Zizzo (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2008)
This paper presents an experimental study of dynamic indefinite horizon R&D races with uncertainty and multiple prizes. The theoretical predictions are highly sensitive: small parameter changes determine whether technological competition is sustained, or converges into a market structure with an entrenched leadership and lower aggregate R&D. The subjects' strategies are far less sensitive. In most treatments, the R&D races tend to converge to entrenched leadership. Investment is highest when rivals are close. This stylized fact, and so the usefulness of neck-to-neck competition in general, is largely unrelated to rivalry concerns but can be explained using a quantal response extension of Markov perfection.
Keywords: C72; C91; O31; 330; R&D race; innovation; dynamics; experiment; Forschungs- und Technologiepolitik; Betriebliche Forschung; Entscheidung bei Unsicherheit; Innovationswettbewerb; Markovscher Prozess; Gleichgewichtsstabilität; Theorie